Design of Administrative Information Systems Puskesmas (SIAPUS) Sawah Besar District - Asfani, Asfani; Taufik, Ghofar (Politeknik Ganesha Medan, 2019)
The government's commitment to provide health insurance to the wider community is evidenced by the establishment of puskesmas throughout Indonesia. The Ministry of Health of the Republic of Indonesia for Healthier Indonesia, the motto is the motivation of the puskesmas to improve its performance. Puskesmas is a health agency sector that develops rapidly with population growth. Quality of service is a central point of puskesmas. Along with the era of the Industrial Revolution 4.0 marked by the emergence of various digital innovations impacted on the health services of health centers. From observations that have been made previously, there was a gap in current digital system at the puskesmas where patient, poly, doctor, midwife examination, medical records, recipes, drug history, internal referral, laboratory examinations and internal referral feedback scattered in many divisions have not been integrated resulting in slowed service speeds, data sharing, transaction processing, information distribution has not been running optimally. The impact felt by the human resources that run the system in all divisions, including burnout, increased exhaustion, high chance of human error. The solution through the development of digital-based systems is the most appropriate reference in overcoming the obstacles that occur. Puskesmas information system (SIAPUS) is an application that integrates all data and information spread in all divisions easily and is transparent. Security system is the main key to protect data and information. SIAPUS is equipped with a unique code, notification system and is responsive. The benefit principle becomes an important point of SIAPUS implementation that is able to protect data and information effectively and efficiently, patients get comfort in every treatment, improve time and process efficiency and performance in each division or management, sharing data and information is served by a single database management system. In this study, the system development method needed by the author applies the Spiral model, namely: customer communication, planning, risk analysis, engineering, construction and launch, and customer evaluation. The results of the study are expected to produce a better administration information system application that can help the performance of health centers in data processing and public health reporting that can later answer the various problems that have been faced so far.